Upward Income Mobility and Legislator Support for Education Policies - Luna Bellani; Vigile Marie Fabella (Institute of Labor Economics (IZA), 2018)
This paper investigates how upward mobility affects legislator voting behavior towards education policies. We develop an electoral competition model where voters are altruistic parents and politicians are office seeking. In this setting the future economic status of the children is affected both by current public education spending and by the level of upward mobility. Using a newly compiled dataset of roll call voting on California education legislation matched with electoral district-level upward mobility we find that the likelihood of a legislator voting "no" on redistributive education bills decreases by 10 percentage points when upward mobility in his electoral district decreases by a standard deviation.
Keywords: I24; D72; H4; 330; upward income mobility; education policies; legislator voting behavior; roll call votes; California